Prevalence of malnutrition in children under 5 years of age. Comparison between OMS parameters and their adaptation to Colombia - Barrera-Dussán, Nathaly; Ramos-Castañeda, Jorge Andrés (Universidad y Salud, 2019)
Introduction: The World Health Organization (WHO), has established the growth patterns of children under 5 years of age. Colombia has adopted anthropometric indicators and cut-off points to classify nutritional status. However, weight/height are the only measurements taken into account for defining malnutrition, instead of Body Mass Index (BMI). Objective: To identify malnutrition prevalence in children who are younger than 5 years of age and live in the metropolitan area of the municipality of Palermo-Huila (Colombia), comparing the results with the WHO reference standards and with the IMC/Age parameter of Resolution 2465 of 2106. Materials and methods: A cross-sectional study with an analytical approach was conducted on 254 children younger than 5 years old from Palermo. Results: According to the BMI/Age parameter 11.81% of the children showed some nutrition problem: 1.9% malnutrition and 9.8% overweight and obesity. 25.5% of children were at risk of having some type of malnutrition, with the risk of overweight (17.7%) being the highest. According to WHO parameters, 12.2% of child participants showed malnutrition: 9.8% due to excess and 2.4% because of a deficient intake of nutrients. It was observed that 18,5% and 7,9% of the minors were at risk of being overweight and underweight, respectively.